Exploiting elastic buckling of high-strength gold nanowire toward stable electrical probing - Seo, Jong Hyun; Kang, Sung Gyu; Cho, Yigil; Park, Harold S.; Yoo, Youngdong; Kim, Bongsoo; Choi, In Suk; Ahn, Jae Pyoung (iScience, 2022)
Buckling is a loss of structural stability. It occurs in long slender structures or thin plate structures which is subjected to compressive forces. For the structural materials, such a sudden change in shape has been considered to be avoided. In this study, we utilize the Au nanowire's buckling instability for the electrical measurement. We confirmed that the high-strength single crystalline Au nanowire with an aspect ratio of 150 and 230-nm-diameter shows classical Euler buckling under constant compressive force without failure. The buckling instability enables stable contact between the Au nanowire and the substrate without any damage. Clearly, the in situ electrical measurement shows a transition of the contact resistance between the nanowire and the substrate from the Sharvin (ballistic limit) mode to the Holm (Ohmic) mode during deformation, enabling reliable electrical measurements. This study suggests Au nanowire probes exhibiting structural instability to ensure stable and precise electrical measurements at the nanoscale.
Keywords: Materials science; Mechanical processing; Mechanics of materials